Effect of preoperative anxiety on postoperative pain in patients undergoing elective lower-segment cesarean section under spinal anesthesia: A cross-sectional study in South India - Yuvashree Suresh; Aswini Lakshminarasimhan (Journal of Current Research in Scientific Medicine, 2022)
Background: Anxiety is often encountered but overlooked in patients undergoing elective surgery. Anxiety may influence the perception of postoperative pain which is one of the major concerns for all patients. This study aimed to evaluate the effect of preoperative anxiety on postoperative pain and to find if any relation exists between demographic variables and anxiety in cesarean patients. Methodology: One hundred and twelve patients undergoing elective cesarean section under spinal anesthesia were evaluated for preoperative anxiety on the day before surgery using the Amsterdam Preoperative Anxiety and Information Scale questionnaire-based face-to-face interview, and postoperative pain was recorded every 6 h after surgery for 24 h using the Visual Analog Scale (VAS). Results: The prevalence of preoperative anxiety in the study subjects was 36%. The need for high information was 22%. The mean for anesthesia-related anxiety, information desire component, combined anxiety score, and VAS scores was 4.21 ± 2.63, 3.23 ± 2.15, 8.72 ± 4.60, and 5.30 ± 1.86, respectively. Postoperative pain was found to be correlating with higher levels of preoperative anxiety (r = 0.25, P < 0.01). Information desire component was found to have a positive, moderate, and significant correlation with anxiety score (r = 0.49, P < 0.01). No statistically significant relationship was found between sociodemographic characteristics and preoperative anxiety. Conclusion: This study demonstrated a positive and statistically significant correlation between preoperative anxiety and postoperative pain. Well-conducted randomized controlled studies are required to determine whether reducing anxiety before a surgery results in reduced postoperative pain response. Anxiety-reducing measures can be employed throughout the preoperative period in the surgical population to reduce postoperative pain in addition to analgesics.